PERLINDUNGAN HUKUM TERHADAP HAK WARIS ANAK ANGKAT DALAM SISTEM HUKUM PERDATA INDONESIA DAN PERSPEKTIF HUKUM ISLAM - RAHMAN, AURELIA MAULIDYA FITRATHUNNISA (Ganec Swara, 2025)
This study aims to analyze the differences in the protection of the inheritance rights of adopted children in the two legal systems and to explore the potential for harmonization between the two. With a normative and comparative legal approach, this study highlights the legal uncertainty faced by adopted children and the need for legislative reform to provide fairer and clearer protection. The findings of this study are expected to contribute to efforts to improve regulations related to the inheritance rights of adopted children in Indonesia. This study uses a normative legal approach that aims to analyze in depth the legal protection of the inheritance rights of adopted children in the Indonesian civil law system and the perspective of Islamic law. The normative legal approach focuses on the study of relevant laws and regulations, including regulations governing adoption and inheritance rights, as well as the principles of Islamic law governing inheritance. This study aims to provide a clear picture of the differences and similarities in legal protection for adopted children in both legal systems. The objectives to be achieved in order to find out, understand; what is the Role of Law on the Inheritance Rights of Adopted Children in the Indonesian Civil Law System and the Perspective of Islamic Law with the conclusion of the study This study contributes to a deeper understanding of the inheritance rights of adopted children in the perspective of Indonesian civil law and Islamic law. This study also opens up space for discussion on the need for adjustments in the Indonesian legal system so that the rights of adopted children can be more guaranteed, considering the increasingly complex social developments